Baekdudgegan the great Baekdu meridian [videorecording] - Jung, Hyung Gun.; Kim, Ki-Dong.; On, Seung-In. ([S.l.] Arirang TV)
A journey to the mountain range from Mount Chini, Mount Dukyu, Mount Taebaek, Mount Odoe and Mount Surak. A look at the traditional tea house and the buddhist ritual.
This program is sponsored by Korea Foundation.
VHS.
Director of photography, Jong-Chan Park, Yeung-Koo Kim, Editor, Duk-il Kim ; Narrator, Michael Irwin.
Keywords: Mountains -- Korea; Rites and rituals -- Korea; Korea -- Description and travel; Korea -- Social life and customs